Construction of recombinant plasmid of chicken calbindin-D28k - YU Lu; WANG Ya-qian; ZHANG Shi-yuan; LI Yan-wu; LI Zhi-xue (浙江大学学报. 农业与生命科学版)
To construct the eukaryotic expression vector of pCEP4-CaBP-D28k, a pair of primers was designed according to chicken calbindin-D28k (CaBP-D28k) gene sequence published in GenBank. Chicken CaB P-D28k gene was amplified by RT-PCR from chicken intestine total RNA extracts and was cloned into eukaryotic expression vector pCEP4, and transferred into COS-1, The gene expression was detected by indirect immunofluorescent assay (IFA). The result shows that the cloned CaBP-D28k gene, encoding 261 amino acids, was 789 bp in length which was 99.9% identity but only one nucleotide changed from G to T at site 760 compared with published sequence from GenBank database. The homology of CaBP-D28k gene sequence between chicken and other species such as frog, house mouse, human was 79.7%, 78.2%, 78.6%, respectively; the target segment in recombinant plasmid was characterized and confirmed by restrictive endonuclease assay as well as sequence analysis. The expression of CaB P-D28k could be detected in COS-1. This research provides a novel means to study regulation mechanism of calcium metabolism in chickens through pCEP4-CaBP-D28k.